If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1b = -4 Solving 1 + -1b = -4 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1b = -4 + -1 Combine like terms: 1 + -1 = 0 0 + -1b = -4 + -1 -1b = -4 + -1 Combine like terms: -4 + -1 = -5 -1b = -5 Divide each side by '-1'. b = 5 Simplifying b = 5
| x(x+1)(x+2)=504 | | x^3+3x^2+2x-504=0 | | 500=2x+y | | 3(x-1)-2(x-3)=20 | | X=4+1.5y | | 3(4/5)-1(3/4) | | 34/5-13/4 | | 64=a^2+100 | | x/4=5/4x | | ((x-5)/(4x^2-9))*((4x^2+12x+9)/(2x^2-11x+5)) | | 0.2y=4.8 | | 280+4x=12x | | 4*x-8=0 | | 17-3a+5a=-8+6+9a | | y-7.3=5.5 | | 5.5+y=7.3 | | 22p-17=12p+8 | | 22p-17=12p | | 2y+5=23 | | 6(7-x)+x=-15 | | 6+0=66 | | 7x+114=(3x+16)2 | | 135792468*246813579= | | 7x+144=(3x+16)2 | | 7+1=57 | | 8+2=610 | | 5x-3(4x-3(4x-3(5x-2)))=182 | | f(x)=a^2+b | | 6x+2y=180 | | 2w^2+11w+15= | | 2w^2-2w+41=0 | | 5x=185 |